The impact of COVID-19 on the economic and accounting transformation - M.P. Horodyskyi; D.M. Zakharov; І.V. Оrlov (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The coronacrisis accelerated the process of economic digitization. New technologies are changing approaches to the organization of labor, as a result of a process of changing classic business models. The competitive environment in all market sectors is changing. Businesses at all levels are working to integrate technology for creating a sustainable, mobile, and digital business model. Accordingly, to ensure this process, technical support in the form of data hubs, data centers, etc. is required. ISSN 1994-1749. 2020. Вип. 3 (47) Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу 70 Strategies of digitalization of different countries are considered. It is determined that the digitization process provides these basic factors for the beginning of qualitative changes: infrastructure upgrades, expansion of databases, widespread mobile devices with a high level of communication capabilities, increasing accessibility and expanding the use of the Internet. As a result, digitalization leads to a general «connection» and the total impact of these processes on all sectors of the economy: industry, transport, finance, health, education, and others. For an objective assessment of performance and business opportunities, it is proposed to include in the management report information on development prospects, key risks, the achievement of declared goals, and strategic plans, taking into account the degree of consequences caused by the COVID-19 pandemic. Businesses should review their accounting and reporting policies to provide accurate and up-to-date information on stakeholder performance.